The impact of dollar price fluctuations on the GDP of developing countries: Iraq as a model - Hameed, Mutawakkil Mansur; Karim, Yahya Farouk; Kareem, Maitham Sami (Edelweiss Applied Science and Technology, 2024)
The exchange rate is a tool of monetary policy, which is a matter of monetary policy, determined by the Central Bank of Iraq, as well as the subject of the exchange rate of complex topics, and the importance of this research lies in understanding the impact of dollar price fluctuations on the Iraqi economy, which contributes to enhancing knowledge about how external factors interact with local economic conditions, providing valuable recommendations for decision-makers to design effective strategies to deal with these fluctuations and achieve greater economic stability. The descriptive approach was used to collect and analyze economic data related to dollar price fluctuations and its impact on GDP, which helps to understand the relationships between these variables in Iraq during the period (2003-2024), the most important conclusions reached by the research that the general trend indicates sustainable growth in GDP, but economic challenges, such as exchange rate fluctuations and inflation, need to be effectively addressed. The government and central bank should promote economic stability through effective monetary policies that support growth and maintain exchange rate stability.